Alcohol intake and breast cancer in the European prospective investigation into cancer and nutrition. Issue 8 (14th July 2015) - Romieu, Isabelle; Scoccianti, Chiara; Chajès, Véronique; de Batlle, Jordi; Biessy, Carine; Dossus, Laure; Baglietto, Laura; Clavel‐Chapelon, Françoise; Overvad, Kim; Olsen, Anja; Tjønneland, Anne; Kaaks, Rudolf; et al.
<x xml:space="preserve">Abstract</x> Alcohol intake has been associated to breast cancer in pre and postmenopausal women; however results are inconclusive regarding tumor hormonal receptor status, and potential modifying factors like age at start drinking. Therefore, we investigated the relation between alcohol intake and the risk of breast cancer using prospective observational data from the European Prospective Investigation into Cancer and Nutrition (EPIC). Up to 334, 850 women, aged 35–70 years at baseline, were recruited in ten European countries and followed up an average of 11 years. Alcohol intake at baseline and average lifetime alcohol intake were calculated from country‐specific dietary and lifestyle questionnaires. The study outcomes were the Hazard ratios (HR) of developing breast cancer according to hormonal receptor status. During 3, 670, 439 person‐years, 11, 576 incident breast cancer cases were diagnosed. Alcohol intake was significantly related to breast cancer risk, for each 10 g/day increase in alcohol intake the HR increased by 4.2% (95% CI: 2.7–5.8%). Taking 0 to 5 g/day as reference, alcohol intake of >5 to 15 g/day was related to a 5.9% increase in breast cancer risk (95% CI: 1–11%). Significant increasing trends were observed between alcohol intake and ER+/PR+, ER−/PR−, HER2− and ER−/PR−HER2− tumors. Breast cancer risk was stronger among women who started drinking prior to first full‐time pregnancy. Overall, our results confirm the association between alcohol intake and both hormone receptor positive and hormone receptor negative breast tumors, suggesting that timing of exposure to alcohol drinking may affect the risk. Therefore, women should be advised to control their alcohol consumption.